AGRICULTURAL PRODUCT LOGISTICS AND THE ADVANTAGES OF ITS EFFICIENT USE - Olimova Bahora Shukhratovna (Web of Journals Publishing, 2025)
This article provides a detailed analysis of the logistics of agricultural products and the advantages of their effective management. The study examines opportunities to increase production efficiency, optimize resource utilization, and enhance economic benefits through the optimization of agricultural product supply systems. The article highlights the development of information technologies, innovative logistics systems, and transport and storage infrastructure as crucial factors. The research presents challenges in Uzbekistan's agricultural logistics system and recommendations for their resolution, as well as approaches based on global practices. This article offers relevant information for specialists interested in scientific and practical outcomes in the field of agricultural logistics.
Keywords: Agricultural products, logistics system, effective management, transport infrastructure, innovative technologies, information systems, production efficiency, export, resource optimization, economic development.